A diketopyrrolopyrrole-based fluorescence turn-on probe for the detection of Pb2+ in aqueous solution and living cells. Issue 57 (27th May 2016) - Yang, Xiaofeng; Zhang, Yan; Li, Yexin; Liu, Xiaolei; Mao, Jiaxin; Yuan, Yuan; Cui, Yu; Sun, Guoxin; Zhang, Guangyou
Abstract : A diketopyrrolopyrrole-based fluorescent probeDPP-HBT bearing a benzothiazole hydrazone motif exhibited an obvious fluorescent turn-on response toward Pb 2+ ions with a low detection limit of 2.3 × 10 −10 M in aqueous solution. Abstract : A diketopyrrolopyrrole-based fluorescent probeDPP-HBT bearing a benzothiazole hydrazone motif exhibited an obvious fluorescent turn-on response toward Pb 2+ ions with a low detection limit of 2.3 × 10 −10 M in aqueous solution. Furthermore, the imaging experiments indicated that this probe was cell-permeable and could be used to detect Pb 2+ ions within living cells.